Educational Thoughts of Dewi Sartika: Study of Analysis of Islamic Education Values - Tumanggor, Syahwan; Nurul Asyikin; Amriansyah Pohan (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: National History has recorded at least some big names behind the Indonesian educational mindset, one of which is Dewi Sartika. Dewi Sartika is a figure who fights for women's education. A distinctive pattern in the thought and practice of Dewi Sartika's education is the integration of general science with religious values. This type of article research is library research. The article is prepared with a descriptive-critical method with more emphasis on the power of analysis of existing sources and data. The results showed that the thought and practice of Dewi Sartika's education contained so many Islamic values. This can be seen from the thoughts, vision and mission, ideals, goals, and educational practices that have been carried out by Dewi Sartika.   Abstrak: Sejarah Nasional telah mencatat setidaknya beberapa nama besar di balik pola pikir pendidikan Indonesia, salah satunya adalah Dewi Sartika. Dewi Sartika adalah sosok yang memperjuangkan pendidikan perempuan. Pola yang khas dalam pemikiran dan praktik pendidikan Dewi Sartika adalah integrasi ilmu umum dengan nilai-nilai agama. Jenis penelitian artikel ini adalah penelitian kepustakaan. Artikel ini disusun dengan metode deskriptif-kritis dengan lebih menekankan pada kekuatan analisis sumber dan data yang ada. Hasil penelitian menunjukkan bahwa pemikiran dan praktik pendidikan Dewi Sartika mengandung begitu banyak nilai-nilai Islam. Hal ini dapat dilihat dari pemikiran, visi dan misi, cita-cita, tujuan, dan praktik pendidikan yang telah dilakukan oleh Dewi Sartika. Kata Kunci: Pendidikan, Pemikiran, Dewi Sartika